SOCIAL REHABILITATION OF JUVENILE OFFENDERS. - Melkumyan, Yuliana (Journal of Sociology: Bulletin of Yerevan University, 2019)
The period of life between childhood and adulthood is characterized by intense transformations of consciousness, the system of values and interests. Therefore, social rehabilitation of juvenile offenders is not only an important but also an extremely complex process. The article analyzes the possibilities of social rehabilitation of juvenile offenders in the framework of Merton’s theory of social anomie and Festinger’s theory of cognitive dissonance.